An image processing system for detecting production errors on circuit boards and enabling error tracking and reporting based on 2-D barcodes [Görüntü işleme ile devre dizgi hatalari tespitine ve 2-b barkod tabanli takip ve raporlamaya yönelik bir sistem tasarimi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In this study, the system is designed to detect the assembly errors of the circuit board in serial production. The system consists of a low cost camera, lighting equipments and an embedded system which provides control and communication function with computer software. Two desktop software are developed to set-up golden circuit board(reference board) and the error detection algorithms. Operator uses operator software via user interface. This program performs checking of errors on the tested circuit board using the data saved by the administrator software. At the same time, operator software saves test results to the database while reading datamatrix code on each circuit board. Test results which made on 100 circuit board in the Electronic R&D laboratory show that analysis operations are performed at least %87 accuracy. © 2018 IEEE.
Keywords: Datamatrix barcode; Embedded system; Image processing; Lighting